1996
DOI: 10.1063/1.362634
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of defects in self-ion implanted Si using positron annihilation spectroscopy and Rutherford backscattering spectroscopy

Abstract: The behavior of vacancy-type defects and displaced Si atoms in Si(100) caused by self-ion implantation has been investigated by variable-energy positron annihilation spectroscopy and Rutherford backscattering spectroscopy/channeling. It is found that the recovery process of the defects strongly depends on the morphology of the implanted region. The divacancies produced by an implantation of 2×1014Si+⋅cm−2, which is less than the critical value required for amorphization, aggregate into large vacancy clusters b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…1. This behavior is consistent with earlier observations on the stability of vacancy clusters up to 500 C and their annealing at higher temperatures [2,5,7].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…1. This behavior is consistent with earlier observations on the stability of vacancy clusters up to 500 C and their annealing at higher temperatures [2,5,7].…”
supporting
confidence: 93%
“…However, Makhov and Lewis later suggested that vacancy clustering may well not lead to a clear change in PAS parameters, while the IR response is destroyed [6]. In another study of near-surface implantation-induced V 2 in Cz-Si it was found that if the ion dose is below the critical value for amorphization, vacancy clusters form after annealing at 300 C, which are stable up to 500 C but anneal out at 800 C [7].…”
mentioning
confidence: 99%
“…The existence of such a layer has been identified previously using PAS for implanted elements not lighter than fluorine, and is postulated to be due to diffusion of defects. 18,19 In addition, a layer with an electric field of Ϫ1 kV/cm was required near the surface ͑up to 1 m͒ to model the effect of the charge in the native oxide at the sample surface. Modeling of such fields has previously been discussed by Simpson et al 20 for Si wafers with various dopant concentrations and types.…”
Section: Methodsmentioning
confidence: 99%
“…The interested reader may look into review articles on this subject [31][32] and the references therein. A few references are cited at the end [33][34][35][36][37][38][39][40] .…”
Section: Discussionmentioning
confidence: 99%